The Biophysics of Cancer: Emerging Insights from Micro‐ and Nanoscale Tools. Issue 1 (23rd November 2021) - Beshay, Peter E.; Cortes-Medina, Marcos G.; Menyhert, Miles M.; Song, Jonathan W.
Abstract : Cancer is a complex and dynamic disease that is aberrant both biologically and physically. There is growing appreciation that physical abnormalities with both cancer cells and their microenvironment that span multiple length scales are important drivers for cancer growth and metastasis. The scope of this review is to highlight the key advancements in micro‐ and nanoscale tools for delineating the cause and consequences of the aberrant physical properties of tumors. Herein, the following three important physical aspects of cancer are focused: 1) solid mechanical properties, 2) fluid mechanical properties, and 3) mechanical alterations to cancer cells. Beyond posing physical barriers to the delivery of cancer therapeutics, these properties are also known to influence numerous biological processes, including cancer cell invasion and migration leading to metastasis, and response and resistance to therapy. There is a comment on how micro‐ and nanoscale tools have transformed the fundamental understanding of the physical dynamics of cancer progression and their potential for bridging toward future applications at the interface of oncology and physical sciences. Abstract : Inspired by the emerging importance of physical properties and mechanical forces in cancer, herein the key advancements of micro‐ and nanoscale tools with biological integration for advancing cancer biophysics research are examined. Perspectives on how these tools provide functional responses, measurements, and biological readouts for studying the complex and dynamic multiscale interactions that underlie cancer progression are provided.